Enjoying nutrient rich capsicum and karonda salsa - Karel, Archna; Singh, Balraj (Indian Horticulture, 2019)
Indian population is mostly vegetarian, therefore we depend on cereals, pulses, vegetables, fruits and dairy products for energy as well as nutrient supplementation. The burden of micronutrient malnutrition is very high in India. Food fortification of staples is one means of addressing this problem. The other may be consumption of fruits and vegetables containing diverse antioxidants, which protect against diseases. Proper nutrition promotes the optimal growth and development of children.